2017
DOI: 10.1002/jbm.b.33873
|View full text |Cite
|
Sign up to set email alerts
|

Transcortical or intracondylar? Which model is accurate for predicting biomaterial attachment in total joint replacement?

Abstract: Despite four decades of research on material and porous coatings intended for cementless fixation in total joint replacement (TJR), aseptic mechanical loosening unrelated to particulate disease remains a concern. One main question asked is how translational are the animal models used to screen material and porous coatings intended for TJR fixation? Another question is how specific are the translational models at targeting the cementless TJR components that have the highest loosening rates? The hypothesis teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The biological healing zone only appeared to influence 100–200 μm of bone in the periprosthetic region of the porous‐coated plugs, suggesting the host tissue was relatively unaffected by the porous‐coated plug placement. This coincides with Bloebaum et al, which reported that the osteoblastic jumping distance of cancellous bone from the surgically prepared surface was ~169 μm in a similar translational cancellous bone model (Bloebaum et al, ). The observed unaltered host bone was confirmed with light microscopy analysis which reveled healthy bone marrow in the adjacent host trabeculae as well as osteoblast activity within both porous coating types.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The biological healing zone only appeared to influence 100–200 μm of bone in the periprosthetic region of the porous‐coated plugs, suggesting the host tissue was relatively unaffected by the porous‐coated plug placement. This coincides with Bloebaum et al, which reported that the osteoblastic jumping distance of cancellous bone from the surgically prepared surface was ~169 μm in a similar translational cancellous bone model (Bloebaum et al, ). The observed unaltered host bone was confirmed with light microscopy analysis which reveled healthy bone marrow in the adjacent host trabeculae as well as osteoblast activity within both porous coating types.…”
Section: Discussionsupporting
confidence: 89%
“…The radiography demonstrated well‐placed plugs with good bone‐implant contact for both porous coating types at Time = 0 with the exception to a single CoCr plug that only achieved ~50% ABI due to surgical error. This observation emphasizes the need for precision operative placement of porous‐coated devices to achieve initial bone implant‐contact to avoid gaps that can lead to fibrous tissue being interposed between the coating and host trabeculae (Bloebaum et al, ). The lower ABI in this lone plug was shown to be due to over drilling at the time of surgical placement and was not indicative of the porous coating material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New bone was observed in the cancellous gap sites in the Ti HA group that could be attributed to the presence of the calcium phosphate coating and local biological benefits [8,36]. This effect was particularly apparent at the early (4 week [7, 8, 12-14, 25-28, 37, 38] and dogs [11,15,[39][40][41] as well as cancellous sites as performed in this study [12,13,26,28] and intercondylar sites [37,38,42]. Care should always be taken when making Titanium alloy coated with plasma sprayed titanium.…”
Section: Resultsmentioning
confidence: 52%
“…Preclinical studies have limitations but allow for tighter control of variables such as animal age, implant geometry, and implantation conditions that can help identify the advantages as well as disadvantages of different technologies. A variety of large animal preclinical models have been used to examine the bone- implant interface with cylindrical dowels to evaluate bone ingrowth and ongrowth to different materials and surface coatings in cortical sites in sheep [7, 8, 12-14, 25-28, 37, 38] and dogs [11,15,[39][40][41] as well as cancellous sites as performed in this study [12,13,26,28] and intercondylar sites [37,38,42]. Care should always be taken when making the jump to the human clinical scenario.…”
Section: Discussionmentioning
confidence: 99%